THE EFFECT OF BRAND IMAGE AND CUSTOMER RELATIONSHIP ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION AT AL-ULUM PRIMARY SCHOOL - Dian Setyorini; Satria Tirtayasa; Hazamanan Khair (Jurnal Ekonomi, 2023)
This study aims to determine the effect of brand image and customer relationship on customer loyalty mediated by customer satisfaction. The population of this study was all parents of Al-Ulum Primary School students, using the slovin formula as a sampling technique. Data analysis techniques using path analysis. The results of this study indicate that brand image has a significant effect on consumer satisfaction. Customer Relationship has a significant effect on Consumer Satisfaction. Brand Image has a significant effect on Customer Loyalty. Customer Relationship has a significant effect on Customer Loyalty at Al-Ulum Primary School . Consumer Satisfaction has a significant effect on Customer Loyalty at Al-Ulum Primary School . Consumer Satisfaction can mediate the effect of Brand Image on Customer Loyalty. Consumer Satisfaction can mediate the influence of Customer Relationships on Customer Loyalty.